Measurement of double-differential thick-target neutron yields of the C(d, n) reaction at 12, 20, and 30 MeV. Issue 2 (1st February 2021) - Patwary, Md Kawchar Ahmed; Kin, Tadahiro; Aoki, Katsumi; Yoshinami, Kosuke; Yamaguchi, Masaya; Watanabe, Yukinobu; Tsukada, Kazuaki; Sato, Nozomi; Asai, Masato; Sato, Tetsuya K.; Hatsukawa, Yuichi; Nakayama, Shinsuke
ABSTRACT: While designing deuteron accelerator neutron sources for radioisotope production, nuclear data for light elements such as Li, Be, and C have been systematically measured in the deuteron energy range from a few MeV to around 50 MeV. Currently, the experimental data available on double-differential thick-target neutron yields (DDTTNYs) are insufficient, especially for deuteron energies between 18 and 33 MeV. In this study, we measured the DDTTNYs of ( d, n ) reactions on nat C target for incident deuteron energies of 12, 20, and 30 MeV using the multiple-foil activation method to improve nuclear data insufficiency. The neutrons were detected at emission angles of 0°, 10°, 20°, 30°, and 45°. We applied the GRAVEL code for the unfolding process to derive the DDTTNYs. The results were compared with the calculation by the deuteron-induced reaction analysis code system (DEURACS), and the DEURACS calculation underestimated our results 12 and 20 MeV deuteron. The present data were also used to confirm the systematics of the differential neutron yields at 0° and total neutron yield per incident deuteron in 12–30 MeV of deuteron energy.